2011
DOI: 10.1371/journal.pone.0022112
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte Hypertrophy, Fatty Liver and Metabolic Risk Factors in South Asians: The Molecular Study of Health and Risk in Ethnic Groups (mol-SHARE)

Abstract: ObjectiveWe sought to determine if differences in the distribution and characteristics of adipose tissue between South Asians and white Caucasians account for differences in risk factors for cardiovascular disease.Research Design and MethodsWe recruited 108 healthy South Asians (36.8 years) and white Caucasians (34.2 years) within three BMI strata. Body composition, adipocyte size, abdominal fat area, and hepatic adiposity were assessed and related to fasting glucose, insulin, lipids and adiponectin.ResultsAft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
149
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(160 citation statements)
references
References 32 publications
8
149
2
1
Order By: Relevance
“…However, our findings are in accordance with a study that found no differences in deep or superficial subcutaneous fat between Norwegian and Pakistani women with type 2 diabetes (35). On the other hand, South Asians have been found to have larger adipocyte size (36), which, in turn, has been associated with insulin resistance and hyperleptinemia (37) and type 2 diabetes independently of insulin resistance (38). Therefore, the relative amount of subcutaneous fat may be the same, while the number of adipocytes may be lower and the adipocytes larger in South Asians vs Europeans.…”
Section: European Journal Of Endocrinologysupporting
confidence: 93%
“…However, our findings are in accordance with a study that found no differences in deep or superficial subcutaneous fat between Norwegian and Pakistani women with type 2 diabetes (35). On the other hand, South Asians have been found to have larger adipocyte size (36), which, in turn, has been associated with insulin resistance and hyperleptinemia (37) and type 2 diabetes independently of insulin resistance (38). Therefore, the relative amount of subcutaneous fat may be the same, while the number of adipocytes may be lower and the adipocytes larger in South Asians vs Europeans.…”
Section: European Journal Of Endocrinologysupporting
confidence: 93%
“…However, smoking and obesity rates remain high and should be the target of public health programmes. [16][17][18] For south Asian patients, the cut-off for being obese was set at a BMI of over 25 kg/m 2 . For patients who were not south Asian, the cut-off was set at a BMI of >30 kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
“…6,8 Also, South Asians living in Canada had greater fasting insulin, lower high-density lipoprotein cholesterol (HDL-C), lower adiponectin, greater body fat, lower lean body mass, and more hepatic fat compared to Caucasians, after adjusting for age, sex, and body mass index (BMI). 9 Our research group has also found that disease risk is apparent in rural Nepali women, even at normal BMI and waist circumference (WC) levels. 10 The World Health Organization (WHO) Global Status Report focused on eight risk factors for NCDs: (1) Tobacco use, (2) harmful use of alcohol, (3) unhealthy diet, (4) raised blood pressure, (5) overweight and obesity, (6) raised cholesterol, (7) inadequate physical activity, and (8) cancerassociated infections.…”
mentioning
confidence: 92%